Memória e ancestralidade: as vozes na "escrevivência" de Conceição Evaristo e Eliane Potiguara - Lima, Débora Francisca de (2022)
The aim of this work is to investigate how memory, ancestry, and writing are experienced in the work Metade Cara, Metade Máscara, by Eliane Potiguara; and Poemas Recordação e outros movimentos, by Conceição Evaristo, and how violence is intertwined as a category of silencing. The voices of these two women recreate one of the aspects of the worldview of black and indigenous writing – ancestry. Our main interest in analyzing the works centralized into two aspects. The first was the analysis of the poetic images constructed. Ancestry, that invisible trait, which spans generations, anchors poetics; subjectivity is elaborated in the writing of the self, “escrevivências”, poetic material used by both. Another aspect embraced was how these contemporary literatures dialogue with their ethnic groups and the importance of studying the coloniality of power and decoloniality for a better understanding of these literatures. An ethnic cosmovision is perceived in which female writers insert themselves in the literary universe with a sharp and tender feminine look around issues such as: violence, racism, subalternization and engender a form of resistance - literary writing. Potiguara and Evaristo intend to denounce the practice of exclusion, infiltrated in everyday life, in the situation of domination experienced by blacks and indigenous people.The paper proposal is based on a theoretical corpus on memory, ancestry, as well as performance, decoloniality, black and indigenous representations, since these elements are built on the experience of these women in the construction of their subjectivities. To extend de compreheension of the theme, authors with recognized contributions to the study of characters and performance will be used, such as Cândido, Silva, Zumthor, among other academic works that deal with the theme of memory and identity, such as Selligmann-Silva and Maluf, authors who talk about decoloniality like Mignolo and Quijano, about indigenous representation like Graúna, Kambeba and Krenak, among others.Black and indigenous literature make up the diversity of contemporary manifestations, and in this plurality they seek inclusion in the literary context, different from the exclusion to which they were subjected. Understanding the enunciation roles of black and indigenous women in the current literary context implies looking at the literature of these women without the stigma of color and ethnicity and without the attempt to establish a standard of reading/interpretation.